PROMOTING SAFE EDUCATION ENVIRONMENTS: EFFECTIVENESS OF ASSERTIVENESS-BASED BST INTERVENTIONS AGAINST BULLYING - Nor Mita Ika Saputri; Khairul Amri; Husniah Ramadhani Pulungan; Puji Pratiwi (EDUCATIONE, 2025)
Bullying remains a critical concern in Indonesian education, with national and global data highlighting persistently high prevalence rates and profound negative impacts on students’ academic, psychological, and social well-being. This study aimed to evaluate the effectiveness of an assertiveness counseling module, utilizing Behavioral Skills Training (BST), in reducing bullying behavior among students at MTs Muhammadiyah 22 Padangsidimpuan. Employing a pre-experimental, one-group pretest-posttest design, a purposively selected sample of 50 students, representing victims, bystanders, and perpetrators, participated in the intervention. Quantitative data were collected using a validated Bullying Behavior Scale and analyzed with paired-sample t-tests. Results revealed a significant decrease in bullying tendencies post-intervention, with most students shifting from moderate/high to low/very low categories, and a large effect size indicating substantial practical impact. The findings confirm that BST-based assertiveness education is effective in transforming bullying behaviors and fostering a more positive school climate, aligning with evidence from international literature while addressing gaps in culturally relevant interventions for religious and semi-rural educational settings. This research contributes practical guidance for integrating assertiveness training into counseling curricula and underscores the urgent need for skill-based anti-bullying strategies in Indonesian schools. Future studies are recommended to employ randomized controlled trials, expand to multiple school contexts, and examine the long-term sustainability of behavioral change to enhance the generalizability and impact of assertiveness education in preventing bullying.